The Effect of Competence and Accountability on the Performance of Government Auditors - Amsari, Syahrul; Husna, Asmaul (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2022)
The purpose of this study was to utilize the research site of the South Tapanuri Regency Regional Regulatory Authority by taking a sample of 65 auditors and P2UPDs based on the work of the South Tapanuri Regency Regional Government/Municipality to assess APIP performance. is to analyze the capacity and accountability of Data for this study were obtained from the results of questionnaire responses. The survey data were then analyzed using the Partial Least Squares (PLS) analysis technique using the SmartPLS version 3.0 program for Windows. Based on the analytical results of this study, APIP's performance was influenced simultaneously by APIP's ability and responsibility variables. Analysis results show that 64% of APIP's performance is influenced by APIP's competence and accountability.